Existence and regularity results for parabolic equations with degenerate coercivity. Issue 5 (4th May 2018) - El Hadfi, Y.; Benkirane, A.; Youssfi, A.
Abstract: The goal of this paper is to address existence and regularity results for some nonlinear parabolic equations with degenerate coercivity, of the following form where is a bounded domain in with the function f belongs to and the main operator is allowed to degenerate with respect to the unknown u .